STUDENTS’ DESCRIPTIVE WRITING PERFORMANCE: THE ANALYTIC SCORING ASSESSMENT USAGE - Didik Rinan Sumekto; Heny Setyawati (Jurnal Cakrawala Pendidikan, 2018)
Abstract: This study explores students’ performance in descriptive writing. Forty-five English Education sophomore students participated to be the respondents. The data were collected from students’ descriptive writing performance using a 5-Likert scale and they were quantitatively analyzed through the descriptive and factor analysis tests. Students’ descriptive writing were measured through the means of components of grammar, punctuation, coherence, cohesion, and content. Other substantial findings corresponded with the principal component analyses that determined the presence of 5 components with the eigenvalue outreaching 1, positioning 31%, 27.3%, 19.7%, 12.6%, and 9.4% of the variances accordingly. This referred to the factorial analysis that claimed 2 extracted components with a total of 58.32% of the variance. The component 1 was 31.00% and component 2 was 27.32%. The interpretation of these components is coherent with the pilot results on the descriptive writing performance scale, in which the component 1 shows the positive affect items and the component 2 partially indicates the negative affect items.  Keywords: Analytic scoring, descriptive writing, factor analysisPENINGKATAN MENULIS DESKRIPTIF MAHASISWA:  PENERAPAN ASESMEN PENSKORAN ANALITIK Abstrak: Penelitian ini mengeksplorasi capaian peningkatan mahasiswa dalam menulis esai deskriptif. Empatpuluh lima mahasiswa pendidikan Bahasa Inggris berpartisipasi sebagai responden. Pengumpulan data diambil melalui hasil esai deskriptif mahasiswa dengan menggunakan 5 skala Likert dan analisis data dilakukan secara kuantitatif melalui uji deskriptif dan analisis faktor. Esai deskriptif mahasiswa diraih melalui rata-rata hitung komponen gramatika, tanda baca, koherensi, kohesi, dan konten. Temuan substansi lainnya terkait dengan analisis komponen utama yang menetapkan 5 komponen dengan raihan 1 nilai eigen yang menempatkan 31%, 27,3%, 19,7%, 12,6%, dan 9,4% varian. Temuan ini merujuk pada analisis faktor dengan 2 komponen yang diraih sebesar 58,32% dari keseluruhan varian, di mana komponen 1 sebesar 31,00% dan komponen 2 sebesar 27,32%. Tafsiran atas dua komponen ini koheren dengan hasil awal skala capaian peningkatan esai deskriptif, di mana komponen 1 menunjukkan butir positif dan komponen 2 menunjukkan sebagian butir negatif.   Kata Kunci: Penskoran analitik, esai deskriptif, analisis faktor